2016
DOI: 10.1523/jneurosci.3157-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ampakine Treatments Stimulate Dendritic Growth and Promote Learning in Middle-Aged Rats

Abstract: Positive allosteric modulators of AMPA-type glutamate receptors (ampakines) have been shown to rescue synaptic plasticity and reduce neuropathology in rodent models of cognitive disorders. Here we tested whether chronic ampakine treatment offsets age-related dendritic retraction in middle-aged (MA) rats. Starting at 10 months of age, rats were housed in an enriched environment and given daily treatment with a short half-life ampakine or vehicle for 3 months. Dendritic branching and spine measures were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 54 publications
1
26
0
1
Order By: Relevance
“…Thus, drug combinations activating these pathways may constitute candidates for enhancing human synaptic plasticity, learning, and memory. Ampakines are another class of drugs that may be effective for augmentation of learning (Lauterborn et al 2016). It would be of interest to examine the efficacy of treatments that combine an ampakine with an activator of ERK, PKA, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, drug combinations activating these pathways may constitute candidates for enhancing human synaptic plasticity, learning, and memory. Ampakines are another class of drugs that may be effective for augmentation of learning (Lauterborn et al 2016). It would be of interest to examine the efficacy of treatments that combine an ampakine with an activator of ERK, PKA, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Losses of large‐diameter and mushroom‐type spines, in contrast, are more closely related to impairments of long‐term memory storage and neurodegeneration, especially in hippocampus (Hara et al, 2012), as observed in Alzheimer's Disease rodent models (Penazzi et al, 2016). Evidence for the inverse exists as well: elevations of both long‐thin and mushroom spines correlate with multiple forms of cognitive enhancement (Kitahara et al, 2016; Lauterborn et al, 2016). This effect was observed within the MML of the dentate gyrus, which along with the outer molecular layer, receives perforant pathway inputs from the entorhinal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has begun to address the question of whether long-term ampakine treatment could be beneficial by assessing if this treatment regimen offsets the deleterious effects of brain aging in hippocampus (Lauterborn et al, 2016). In these studies, 10-month old middle-aged rats were treated with the ampakine CX929 (5 mg/kg in 10% honey in water) or vehicle orally on a 5 day-on / 2 day-off schedule for three months and housed in an enriched environment during this period.…”
Section: Ampakines and Environmental Enrichment Effects On Brain Ageimentioning
confidence: 99%